Penanggulangan Tindak Pidana Desersi di Oditurat Militer (Studi Kasus di Oditurat II-07 Jakarta) - Rismoyo Kurnia Sangkara; Riska Andi Fitriono (Amal Insani Foundation, 2024)
Soldiers of the Indonesian National Army (TNI) are expected to be ready to carry out their duties and obligations and obey the rules and traditions of the command, but it has become a common thing in the military today if soldiers leave their unit without giving reasons or permission from their superiors. In addition to law enforcement activities, the purpose of this study is to identify the factors that contribute to the occurrence of the crime of desertion of TNI members. The method used in this research is Juridical-Empirical research, where information is collected through interviews with people involved in desertion criminal cases as well as by accessing literature data related to this research. The results showed that there are two main factors that cause the criminal act of desertion of TNI members, namely internal factors including mental and emotional states. External factors include the work atmosphere, family environment and economic factors in general which cause TNI to break the law by deserting. In the settlement carried out by the Unit, namely making a Military Police report, the Military Police conducts an investigation and investigation, then the Military Oditur issues an indictment, demands and the Military Court gives a decision. Based on this research, the author provides advice to the Government to pay more attention to the welfare of the TNI and to Military Units that receive applicants for the Indonesian National Army to pay more attention to physical and psychological conditions so that TNI members are more characterized and reflect an authoritative military attitude in the future.